Updates on Sjögren's syndrome: from proteomics to protein biomarkers. (3rd June 2017) - Baldini, Chiara; Cecchettini, Antonella; Gallo, Alessia; Bombardieri, Stefano
ABSTRACT: Introduction : Primary Sjögren's syndrome (pSS) is a complex heterogeneous autoimmune disorder, typically affecting exocrine glands. Recently, a great interest has arisen in searching for novel biomarkers able to improve the diagnostic work-up of the disease as well as the general assessment and the prognostic stratification of pSS patients. From this perspective, salivary proteomics has appeared as a promising tool considering that salivary proteins may closely reflect the underlying disease processes in the salivary glands. Areas covered : Here we will provide an update on the state of the art of proteomics in pSS, focusing in particular on putative novel biomarkers for the disease. There is a special focus on candidate salivary protein and their role in non-invasive diagnosis of pSS. Expert commentary : Proteomics represents an emerging throughput omics-based approach for use in diagnosis of pSS. The studies that have been presented in this review have provided major contributions towards the identification of putative protein biomarkers, that once validated, could be able not only to contribute to a non-invasive diagnosis of pSS but also to the stratification of different disease subsets, ultimately allowing a better comprehension of the disease.